Проблеми створення Одеської губернії в контексті модернізаційних процесів в Російській імперії (60-70-ті роки ХІХ ст.) - Юрій, І. А.; Юрий, И. А.; Jurij, I. (My University, 2012)
The problem of government’s reorganization in the south of Russian empire during reformatory processes of 60 – 70 years of 19 century, origin of creation’s idea within modern Odessa area of a separate administrative and territorial unit with special management and its legal maintenance are considered in the article.
Юрій І. А. Проблеми створення Одеської губернії в контексті модернізаційних процесів в Російській імперії (60-70-ті роки ХІХ ст.) / І. А. Юрій // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 46. – С. 446-454.
Keywords: реорганізація державної влади на півдні Російської імперії у ХІХ ст.; реформаційні процеси 60-70-х років ХІХ ст. у Російській імперії; створення в межах сучасної Одещини окремої адміністративно-територіальної одиниці з особливим управлінням; правове забезпечення існування Одеської губернії; реорганизация государственной власти на юге Российской империи в ХІХ в.; реформаторские процессы 60-70-х годов ХІХ в. в Российской империи; создание в пределах современной Одесщины отдельной административно-территориальной единицы с особым управлением; правовое обеспечение существования Одесской губернии; reorganization of state authority in the south of the Russian Empire in the nineteenth century.; reform processes 60-70-ies of the nineteenth century. in the Russian Empire; the creation of the modern Odessa region within a single administrative-territorial unit with a special control; legal support of the existence of the Odessa province